Implicit Ishikawa Approximation Methods for Nonexpansive Semigroups in CAT(0) Spaces - Zhi-bin Liu; Yi-shen Chen; Xue-song Li; Yi-bin Xiao (Abstract and Applied Analysis)
This paper is devoted to the convergence of the implicit Ishikawa iteration processes for approximating a common fixed point of nonexpansive semigroup in CAT(0) spaces. We obtain the Δ-convergence results of the implicit Ishikawa iteration sequences for a family of nonexpansive mappings in CAT(0) spaces. Under certain and different conditions, we also get the strong convergence theorems of implicit Ishikawa iteration sequences for nonexpansive semigroups in the CAT(0) spaces. The results presented in this paper extend and generalize some previous results.